2018
DOI: 10.1101/342683
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Growth adaptation ofgndandsdhCB Escherichia colideletion strains diverges from a similar initial perturbation of the transcriptome

Abstract: Adaptive laboratory evolution (ALE) has emerged as a new approach with which to pursue fundamental biological inquiries and, in particular, new insights into the systemic function of a gene product. Two E. coli knockout strains were constructed: one that blocked the Pentose Phosphate Pathway (gnd KO) and one that decoupled the TCA cycle from electron transport (sdhCDAB KO). Despite major perturbations in central metabolism, minimal growth rate changes were found in the two knockout strains. More surprisingly, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…However, the diversion of flux away from forming oxaloacetate from fumaric acid by deletion of fumarase genes or overexpression of aspA dramatically reduced the production of L-homoserine, which may attribute to the toxicity of fumaric acids(41).on October 31, 2020 by guest http://aem.asm.org/Downloaded fromIn addition to above rather obvious genetic modifications, we also tested the impact of other different genes on L-homoserine production by using CRISPRi-based gene repression methodology.The results of gene repression indicated that CRISPRi system was a feasible method to regulate gene expression with less labor and time consumption. Specifically, down-regulation of the phosphotransferase system (PTS) is widely approved for reinforcing the biosynthesis of phosphoenolpyruvate (PEP)-derived products(42,43). The repression of zwf, tktA, rpe and talB disrupted the pentose phosphate pathway, which can direct more carbon to the synthesis of precursors in glycolytic pathway.…”
mentioning
confidence: 99%
“…However, the diversion of flux away from forming oxaloacetate from fumaric acid by deletion of fumarase genes or overexpression of aspA dramatically reduced the production of L-homoserine, which may attribute to the toxicity of fumaric acids(41).on October 31, 2020 by guest http://aem.asm.org/Downloaded fromIn addition to above rather obvious genetic modifications, we also tested the impact of other different genes on L-homoserine production by using CRISPRi-based gene repression methodology.The results of gene repression indicated that CRISPRi system was a feasible method to regulate gene expression with less labor and time consumption. Specifically, down-regulation of the phosphotransferase system (PTS) is widely approved for reinforcing the biosynthesis of phosphoenolpyruvate (PEP)-derived products(42,43). The repression of zwf, tktA, rpe and talB disrupted the pentose phosphate pathway, which can direct more carbon to the synthesis of precursors in glycolytic pathway.…”
mentioning
confidence: 99%